(untitled) (Global Journal of Management and Business Research, 2022)
This examination has been completed in the approach of continuous patterns in the hospitality industry in the face of COVID-19 situations Hotel is the Housekeeping Department wills I became the front line of the new general hotel experience after the post COVID-19situations Guests will seek out hotels that prioritise their health and safety by implementing reasonable and systematic cleaning and sanitation procedures Keeping in mind the brain and hygiene protocol there will be strict rules on the part of the hotel to maintain all standard operating processes